Co-simulation model coupling of flexible rope hoisting system and hydraulic braking system for a mine hoist. (June 2022) - Ziyu, Song; Xiaona, Wang; Yajing, Li; Yu, Guo; Huimin, Hao; Jiahai, Huang
The hoist is an important equipment in the mine pit. Since the containers are lifted or lowered with flexible steel wire ropes, there are shocks and vibrations during operation, especially in the emergency braking stage, the shocks and vibration will be more severe. Mine hoist is a complex system; therefore, it is difficult to obtain all its dynamics information only by investigating the flexible hoisting subsystem or hydraulic brake subsystem. Therefore, it is very necessary to establish an accurate model to predict these characteristics of the hoist, this will provide useful tools for hoist design and maintenance. Therefore, a joint modeling methodology is proposed and implemented in this paper. A hoisting system model considering the non-linear factors such as contact characteristics and flexibility was established in RecurDyn. The hydraulic braking system model and control system model were established in AMESim, and the co-simulation model was constructed by the interface module. In this co-simulation model, not only the flexible hoisting subsystem and hydraulic brake subsystem are included, but also the coupling effect of subsystems is considered. Finally, taking the lifting condition as an example, execute emergency braking research on the hoisting system under experiment, mathematical model, and co-simulation model, respectively. Comparing the co-simulation model with the mathematical dynamics model, and the experimental test results, research indicates that the joint simulation model of coupled hoisting system and hydraulic braking system can effectively reflect the dynamic characteristics of the actual hoisting system. It provides an effective tool for hoist design, optimization, performance analysis, and operating condition simulation. In addition, the methods and techniques used in the co-simulation modeling procedure are portable. Therefore, the paper is of significance for the mine hoist.